Professional Learning Community in the Improvement of Student Learning Achievement in a Demonstration School - Wutthisak Bunnaen; Parichart Prasertsang; Wittaya Worapun (Journal of Educational Issues, 2024)
The purposes of the study were to investigate the effects of a professional learning community (PLC) on Thai demonstration school students’ grade point averages and to study and to study students’ satisfaction with the professional learning community to improve their grade point averages. The participants were 107 students in a demonstration school in Thailand who were selected from 1,770 populations in the school as they had lower GPAs than 2.0 in the 4 maximum point system. 107 student caretakers, 89 teachers, and 12 administrators in the same schools also took part in the PLC. The purposive sampling method was used. The instruments were a professional learning community plan and a satisfaction questionnaire. The data were collected during the 2020 academic year. The statistics used in data analysis include percentage, mean score, standard deviation, and a paired samples t-test. It was found that the collaboration between student representatives, parents, teachers, and school management results in extracurricular activities that benefited their learning attitudes and learning achievement. The result could be implicated in educational management as it exemplifies how a professional learning community is formed to serve students’ interests.